Particle flow and reaction plane reconstruction inthe CBM experiment - Mikhaylov V. S. Vasily Sergeevich; Kugler A. Andrey; Kushpil V. Vasily; Tlusty P. Pavel; Seddiki S. Selim; Selyuzhenkov I. V. Ilya Vladimirovich (2015, 2015)
Title screen